Gender, climate change, and group-based approaches to adaptation - Behrman, Julia A.; Bryan, Elizabeth; Goh, Amelia (International Food Policy Research Institute, 2014)
This policy note summarizes the findings of two literature reviews on the gender-differentiated impacts of climate change and the scope for community-based adaptation. It also outlines the framework used to guide these analyses and the other papers summarized in this series.